Samarbeid mellom frivillig sektor og kommunale tjenester på pleie- og omsorgsfeltet. En kvalitativ studie - Solbjør, Marit; Ljunggren, Birgitte; Kleiven, Hanne Hestvik (Nordisk tidsskrift for helseforskning, 2014)
Cooperation between third sector and municipal health care services – a qualitative studyMunicipal health care services are facing challenges due to an increasing number of individuals in need of care, combined with demographic change. More unpaid voluntary work within health care services has been put forward as a solution. Cooperation between volunteers and municipal health authorities can be challenging. This qualitative interview study with seven volunteers and six health care service managers explore experiences with cooperation between third sector and health care services in seven Norwegian regional municipalities. Facilitators for cooperation were predictable economy, municipal coordination, recruitment of volunteers and personal engagement among cooperating parties. Lack of these factors hampered cooperation. Professional expectations towards volunteers were another challenge. In small communities local networks may contribute to recruitment of volunteers and simplify communication between parties. Cooperation towards a common goal may reinforce local identity. This article shows how such cooperation develops in-between formal and informal structures.
Keywords: Frivillig arbeid; samarbeid; pleie- og omsorgssektoren; kommuner; eldre voluntary work; cooperation; municipal health care services; elderly citizens